Intra- and Interindustry Effects of Bank Securities Market Activities: The Case of Discount Brokerage - Saunders, Anthony; Smirlock, Michael (Journal of Financial and Quantitative Analysis, 1987)
Anthony Saunders, Michael Smirlock, Intra- and Interindustry Effects of Bank Securities Market Activities: The Case of Discount Brokerage, The Journal of Financial and Quantitative Analysis, Vol. 22, No. 4 (Dec., 1987), pp. 467-482